Dampak E-Service Quality, Kepercayaan dan Kepuasan Terhadap Niat Pembelian Ulang - Widokarti, Joko Rizkie; Sitaniapessy, Arthur; Sitaniapessy, Harry Anthony Pierre (Public Policy, 2023)
Nowdays, consumer purchasing behavior is increasingly shifting to online purchases which promise a lot of convenience. This study aims to examine the effect of E-Service Quality, Trust, and Customer Satisfaction on repurchase intentions in the context of online purchases on e-commerce sites in Indonesia. The sample size in this study was 177 respondents. Hypothesis testing was carried out using multiple regression analysis. The results showed that e-service quality, customer trust as well as customer satisfaction had a positive impact on repurchase intention.